CORRELATION BETWEEN CLAY CONTENT AND SEED DEPTH IN NO-TILLAGE CORN (Zea mays L.) - WEIRICH NETO, PEDRO HENRIQUE; GARBUIO, PAULO WILLIAM; GIMENEZ, LEANDRO MARIA; COLET, MARCELO JOSÉ (Revista Brasileira de Engenharia de Biossistemas, 2008)
The region of Campos Gerais, in the State of Paraná, is leader in grain yields and state-of-the-art no-tillage farming. The widely adopted no-tillage system tends to increment soil variability. There are several studies about spatial variability of soil characteristics affecting grain yield, but not enough attention has been given to the variability resulting of human actions. The objective of this study was to evaluate the correlation of soil clay content and the depth of placement of corn seeds on areas under no-till systems management. The four selected cornfields areas for the study are property of local farm cooperatives associates. The points for evaluation were defined considering the local mapping of soil texture. Clay content varied from 94 to 489 g kg-1 on Plot 1; from 222 to 414 g kg-1 on Plot 2; from 269 to 509 of rows to be considered for plant distribution and seed depth analyses. The coefficient of variation (CV) of plant distribution was between 23 and 56%. For seed depth, the CV was between 18 and 34%. The regression analysis showed high coefficients of determination (r2) for plots 1 and 2 (r2=0,85 and 0,83). The clay content was generally higher on plots 3 and 4. In this case, the analysis of variance was not significant, and the coefficients of determination were low (r2=0,22 and 0,01). Results indicate that clay content values may be used to delimit g kg-1 on plot 3; and from 368 to 698 g kg-1 on plot 4. The type of planter determined the number management zones on the field, where the depth of seed placing in the planting process can be regulated in different ways.